]]>
LearnNext
##### Get a free home demo of LearnNext

Available for CBSE, ICSE and State Board syllabus.
Call our LearnNext Expert on 1800 419 1234 (tollfree)
OR submit details below for a call back

clear

# Shortcut Method To Find Variance and Standard Deviation

2,604 Views
Have a doubt? Clear it now.
live_help Have a doubt, Ask our Expert
format_list_bulleted Take this Lesson Test

#### Shortcut Method To Find Variance and Standard Deviation - Lesson Summary

Variance of a discrete frequency distribution:   Observation (xi)   x 1   x 2   x 3   ...   x n   Frequency (fi)   f 1   f 2   f 3   ...   f n
Ïƒ 2 = âˆ‘ i = 1 n f i x i - x _ 2 N

Total of the frequencies: N = âˆ‘ i = 1 n f i

Variance of a continuous frequency distribution:

Ïƒ 2 = âˆ‘ i = 1 n f i ( x i - x _ ) 2 N

Total of the frequencies: N = âˆ‘ i = 1 n f i

Many a times, the values of x i in the discrete frequency distribution or the mid-values in the continuous distribution are large. In such cases, there are heavy calculations to find the mean, variance, standard deviation, and so on. To avoid such tedious and time-consuming calculations, step-deviation method by working with an assumed mean is used.

Let the assumed mean be A.
The deviations of the mid-values can be reduced by 1 h  times, where h is the common factor among the mid-values (we usually take the width of the class intervals).
Let the step-deviations be y i =  x i - A h

â‡’  x i = A + h y i                     .... eq (1)

x _ = âˆ‘ i = 1 n f i x i N

x _   = âˆ‘ i = 1 n f i (A + h y i ) N

= A âˆ‘ i = 1 n f i N + h âˆ‘ i = 1 n f i y i N

=  AN N + h âˆ‘ i = 1 n x i y i N                             (âˆµ âˆ‘ i = 1 n f i   = N  )

Let   âˆ‘ i = 1 n f i N   =  y _

âˆ´  x _ = A + h y _                          .... eq(2)
Substituting eq (1) and eq (2) in the formula for the variance, Ïƒ 2 = âˆ‘ i = 1 n f i ( x i - x _ ) 2 N ,

Ïƒ 2 = âˆ‘ i = 1 n f i ( A + hy i - A -  hy _ ) 2 N

Ïƒ 2 = âˆ‘ i = 1 n f i (  hy i -  h  y _ ) 2 N

Ïƒ 2 = h 2 N âˆ‘ i = 1 n f i ( y i - y _ ) 2

The variance deduced is in the term of variable y i.

Hence, this can also be written as: Ïƒ x 2 = h 2Ïƒ y 2.

â‡’ Ïƒ x = hÏƒ y

Ïƒ x  = N âˆ‘ f i y i 2 - ( âˆ‘ i = 1 n f i y i ) 2

(âˆµ Ïƒ y  =  1 N N âˆ‘ f i y i 2 - ( âˆ‘ i = 1 n f i y i ) 2 )